GARRETA BOCHACA, J. (Coord.) (2017). Familias y escuelas. Discursos y prácticas sobre la participación en la escuela. Madrid: Pirámide, 210 páginas, ISBN 978-84-368-3712-4 - Ion Martínez Lorea (Universidad de La Rioja, 2017)
GARRETA BOCHACA, J. (Coord.) (2017). Familias y escuelas. Discursos y prácticas sobre la participación en la escuela. Madrid: Pirámide, 210 páginas, ISBN 978-84-368-3712-4